Towards the optimization of the preparation procedures of PMMA bone cement. Issue 6 (8th December 2015) - Gergely, Ryan C. R.; Toohey, Kathleen S.; Jones, Mary E.; Small, Scott R.; Berend, Michael E.
ABSTRACT: The mechanical properties and thermal history of polymethyl‐methacrylate bone cement vary significantly with the preparation procedure used. Because the polymerization reaction is exothermic, many researchers have attempted to minimize thermal osteonecrosis due to heat generation by altering procedures in the preparation of the cement. In most previous studies, only one or two aspects of the preparation procedure were controlled, and there has been little research that comprehensively examines the effects of preparation on the cure kinetics and resulting properties of bone cement. In this study, cement viscosity, cement layer thickness, initial cement temperature, initial metal component temperature, and mixing method were varied to assess the effects on the cement. Maximum temperature, polymerization time, necrosis index, bending strength, and porosity were chosen to evaluate the different preparation procedures, where an optimal procedure would minimize necrosis, reduce cement cure time, and maximize bending strength. Design of Experiments (DOE) was used to examine the main effects and interactions of preparation techniques. Among the most prominent results, it was found that the cure kinetics and the related quantities are primarily controlled by the initial metal component temperature and that the bending strength is most dependent on the mixing method. For the two formulations studied, the optimum preparation procedures should keep cement and metal components at room temperature prior to mixing with a vacuum mixing system. Reducing cement mantle thickness may also be advantageous, as it reduces the maximum temperature and the risk of tissue damage. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:915–923, 2016.